2022
DOI: 10.1002/cam4.5587
|View full text |Cite
|
Sign up to set email alerts
|

Par14 interacts with the androgen receptor, augmenting both its transcriptional activity and prostate cancer proliferation

Abstract: Background Prostate cancer (PCa) is a major cause of cancer morbidity and mortality for men globally, and androgen signaling clearly drives its onset and progression. Androgen receptor (AR) regulation is complex and remains elusive, despite several studies tackling these issues. Therefore, elucidating the mechanism(s) underlying AR regulation is a potentially promising approach to suppressing PCa. Methods We report that Par14, one isoform of the prolyl isomerases homologous to Pin1, is a critical regulator of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Studies revealed overexpression of Pin1 in both mRNA and protein levels for oral squamous cell carcinoma [143,144], gastric cancer [145], and acute myeloid leukemia [146], and only at the protein level in colorectal cancer [147,148], osteosarcoma [149], and pancreatic cancer [150]. Recently in 2023, Naito et al reported that Par14 is overexpressed in prostate cancer, and it promotes proliferation by directly binding to the androgen receptor and regulating androgen receptor signaling pathways [151]. On the other hand, FKBPs (mainly FKBP51 and FKBP52) and Cyp40 are overexpressed in steroid hormone-dependent cancers such as breast and prostate cancer [152][153][154].…”
Section: Cancermentioning
confidence: 99%
“…Studies revealed overexpression of Pin1 in both mRNA and protein levels for oral squamous cell carcinoma [143,144], gastric cancer [145], and acute myeloid leukemia [146], and only at the protein level in colorectal cancer [147,148], osteosarcoma [149], and pancreatic cancer [150]. Recently in 2023, Naito et al reported that Par14 is overexpressed in prostate cancer, and it promotes proliferation by directly binding to the androgen receptor and regulating androgen receptor signaling pathways [151]. On the other hand, FKBPs (mainly FKBP51 and FKBP52) and Cyp40 are overexpressed in steroid hormone-dependent cancers such as breast and prostate cancer [152][153][154].…”
Section: Cancermentioning
confidence: 99%